Utilizing the Comprehensive Learning Process to Enhance Achievements of Non-formal Primary Education Students - จาริยพานิช ณดล; สำเภาทอง อรุณี (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
The objectives of this research were: 1) to study the learning achievement of non-formal primary education students in the Career Development for Sustainable Living course through the use of an integrated learning process, and 2) to study the satisfaction of non-formal primary education students toward the integrated learning process in the career development course. The population consisted of 30 non-formal primary education students from the Bang Bon District Learning Promotion Center, enrolled in the second semester of the 2023 academic year. The research instruments included an integrated instructional plan for the Career Development for Sustainable Living course, an achievement test, and a 5-point Likert scale satisfaction questionnaire. Data were analyzed using basic statistics, including mean and standard deviation. The research findings revealed that the students’ post-test average score (7.87) was higher than the pre-test average score (5.90). Additionally, the students expressed the highest level of satisfaction with the integrated learning process.